2018
DOI: 10.1111/spol.12386
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the client back in: A comparison between political rationality and the experiences of the unemployed

Abstract: Categorizing the job readiness of unemployed clients is a task of the utmost importance for active labor market policies. Scholarly attention on the topic has mostly focused either on questions of political legitimacy or on how categories are practically negotiated in meetings between the welfare system and the client. This article proposes a comparative methodology, in which the political rationality of job readiness is contrasted with findings from a qualitative longitudinal study into the lived experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Second, if we look at the particular organizational and occupational context of the activation site, the study is, however, also a case of face-to-face encounters between frontline workers with large discretion and little social work education, and social assistance claimants who often feel that their individual concerns are rarely heard (Caswell et al, 2011; Danneris and Nielsen, 2018). Studies of welfare frontline encounters with similar conditions in the US (Maynard-Moody and Musheno, 2003) and France (Dubois, 2010) have shown that such conditions cause frontline workers to change their discretionary decisions on a case-to-case basis and that both clients and frontline workers attempt to establish a trustful relationship.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, if we look at the particular organizational and occupational context of the activation site, the study is, however, also a case of face-to-face encounters between frontline workers with large discretion and little social work education, and social assistance claimants who often feel that their individual concerns are rarely heard (Caswell et al, 2011; Danneris and Nielsen, 2018). Studies of welfare frontline encounters with similar conditions in the US (Maynard-Moody and Musheno, 2003) and France (Dubois, 2010) have shown that such conditions cause frontline workers to change their discretionary decisions on a case-to-case basis and that both clients and frontline workers attempt to establish a trustful relationship.…”
Section: Resultsmentioning
confidence: 99%
“…7.They are officially termed either “job ready” or “education ready,” while the more disadvantaged groups are officially called “activity ready.” On the meaning of these categories see Danneris and Nielsen (2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For one, substantial reforms of employment policies have resulted in the development of welfare-to-work 1 (WtW) approaches that bring forward the primacy of work as a goal for welfare services, currently including individualisation as a tool for servicing individual's needs (which can have both promising and less promising implications) and limiting the provision of welfare, even for the vulnerable unemployed (Brodkin, 2013;Brodkin and Larsen, 2013;Considine et al, 2015;Caswell et al, 2017). Clients that were formerly exempt from work and activation obligations, either due to physical, mental and/or social challenges, are now treated as part of the wider group of unemployed individuals (Lindsay and Houston, 2013;Nielsen, 2015;Caswell et al, 2017;Danneris and Nielsen, 2018). This may have positive implications as these groups have previously been overlooked when including people in the labour market.…”
Section: Introductionmentioning
confidence: 99%
“…. A small sub-strand of studies has examined how employment policies are experienced from the perspective of the unemployed individuals they aim to reach (e.g Marston and McDonald, 2008;Danneris, 2016;Danneris and Nielsen, 2018;McIntosh and Wright, 2018)…”
mentioning
confidence: 99%